1985
DOI: 10.1007/bf02714994
|View full text |Cite
|
Sign up to set email alerts
|

VLA observations of three M 33 supernova remnants at 20 cm

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Blair, Chu & Kennicutt (1988) also give di erent diameters as determined from their echelle spectroscopy. Similarly, higher resolution VLA data (Goss & Viallefond 1985) shows that DDB-7 is substantially smaller than either Long et al or Duric et al report. We also nd a smaller diameter for this source ( 3:5 00 ) from an FeII] image obtained with IRCAM3 at UKIRT.…”
Section: Correlation Of Feii] Luminosity and Snr Propertiesmentioning
confidence: 76%
“…Blair, Chu & Kennicutt (1988) also give di erent diameters as determined from their echelle spectroscopy. Similarly, higher resolution VLA data (Goss & Viallefond 1985) shows that DDB-7 is substantially smaller than either Long et al or Duric et al report. We also nd a smaller diameter for this source ( 3:5 00 ) from an FeII] image obtained with IRCAM3 at UKIRT.…”
Section: Correlation Of Feii] Luminosity and Snr Propertiesmentioning
confidence: 76%
“…By the late 1960s, it was known that some SNRs-notably W28, W44, and IC443-had these masers (25). In the following decade, it was pointed out that 1720-MHz masers could occur in warm molecular gas without the need for pumping by a FIR radiation field (26), suggestive of shocked gas, and that they might be associated with SNR-driven shock waves (27).…”
Section: S C I E N C E ' S C O M P a S Smentioning
confidence: 99%
“…IC 443 has become an especially rich target for molecular line observations, including (Burton et al H 2 1988 ;Richter, Graham, & Wright 1995a) ; CO and HCO ( Dickman et al 1992 ;Tauber et al 1994) ; HCN, CN, SiO, CS, SO, and (Turner et al 1992 ; van Dis-H 2 CO, C 2 H hoeck, Jansen, & Phillips 1993). Weaker evidence for interaction was found in CO observations of W44 andW28 (Wootten 1977, 1981), which were earlier found to be sources of OH 1720 MHz line emission (Goss & Robinson 1968). OH 1720 MHz maser line emission has emerged as a signpost of molecular interaction with the detection of compact OH emission from eight supernova remnants (Frail et al 1996), including W44, IC 443, and 3C 391.…”
Section: Introductionmentioning
confidence: 97%
“…These observations did show CO apparently in the vicinity of the remnant, although they did not conclusively show an interaction (DeNoyer 1983). However, Claussen et al (1997) have found compact OH masers in the direction of the remnant (Ðrst discovered by Goss & Robinson 1968) and Seta et al (1998) have recently found evidence for CO clouds that are interacting with the remnant. The remnant is elongated, with radii of 11 ] 15 pc ; because the present models are spherically symmetric, I take 13 pc for the radius.…”
Section: W 44mentioning
confidence: 99%